Seasonal variation in the root activity and appropriate placement of superphosphate in productive Alphonso mango trees as influenced by application of paclobutrazol - KOTUR, S C (The Indian Journal of Agricultural Sciences, 2014)
In 20-year old productive Alphonso mango (Mangifera indica L.) trees, the intensity of root activity was significantly higher under ‘control’ (236 557 dpm/g dry matter) compared to when paclobutrazol was applied @ 3.75 a.i/tree (220 067). Among the seasons, the highest intensity was observed during late rainy season (434 077) while the least was during early rainy season (66 340). The interaction effect showed that during early rainy and winter having good soil moisture regime, ‘control’ trees showed higher intensity while the reverse was true during drier months of early rainy and summer seasons. Active roots dominated 25 cm depth during early season (76–86%) under paclobutrazol application compared to 60–67% found in ‘control’. During late rainy and summer seasons the active roots were uniformly distributed between 25 and 50 cm depths under both ‘control’ and paclobutrazol treatment. In terms of lateral distance, the active roots predominated 100 cm distance during early rainy season under paclobutrazol treatment. In the following seasons, most of the roots were uniformly distributed between 100 and 200 cm distances. The application of paclobutrazol reduced the intensity of root activity and caused the roots to move closer to the trunk and the soil surface during seasons of higher soil moisture regime. The absorption of P supplied through superphosphate during early- and late-rainy seasons was significantly reduced relative to the untreated ‘control’ trees. In such trees, the fertilizer had to be placed closest to the trunk (between 90–160 cm radial distances) to achieve high absorption of P compared to the farther placements at 160–230 cm and 230–300 cm found optimum for the untreated ‘control’ trees to attain high fertilizer use efficiency as consequence of migration of active roots closer to the trunk (100–200 cm radial distance) and towards surface layer (15 cm depth) especially during late rainy season due to the intervention of growth retardant to overcome alternate bearing habit of Alphonso mango trees. These findings form the basis for evolving practical fertilizer management schedules to the mango growers in such situations after more detailed studies employing conventional (non-tracer) techniques.